Expression of a manganese peroxidase isozyme 2 transgene in the ethanologenic white rot fungus Phlebia sp. strain MG-60 - Yamasaki, Yumi (Springerplus, 2014)
BACKGROUND: The white-rot fungus Phlebia sp. strain MG-60 was proposed as a candidate for integrated fungal fermentation process (IFFP), which unifies aerobic delignification and semi-aerobic consolidated biological processing by a single microorganism based on its ability to efficiently degrade lignin and ferment the sugars from cellulose. To improve IFFP, the development of a molecular breeding method for strain MG-60 is necessary. The purpose of this study is to establish the transformation method for the strain MG-60 and to obtain the over-expressing transformants of lignin-degrading enzyme, manganese peroxidase. FINDINGS: In the present study, the expression vector regulated by Phlebia brevispora glyceraldehyde-3-phosphate dehydrogenase promoter and terminator was constructed. A polyethylene glycol transformation method for the ethanol-fermenting white-rot fungus Phlebia sp. MG-60 was established with high transformation efficiency, and the manganese peroxidase isozyme 2 gene (MGmnp2) transformants were obtained, showing higher MnP activity than control transformants. MGmnp2 transformants showed higher selective lignin degradation on Quercus wood powder. CONCLUSIONS: This first report of MG-60 transformation provides a useful methodology for widely accessible to interested researches. These results indicate the possibility of metabolic engineering of strain MG-60 for improving IFFP. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/2193-1801-3-699) contains supplementary material, which is available to authorized users.